Diagnosis and Factors Causing the Incidence of Diarrhea in the Community of Senteluk Village Tourism Area, Batu Layar, West Lombok Regency - Rozikin, Rozikin; Wiatma, Deny Sutrisna (Samota Journal of Biological Sciences, 2024)
Recurrent or widespread diarrhea in the community is a significant health burden, especially for children and the elderly. This study will determine the priority of medical health problems in the community of Senteluk village tourism area and trace the factors that cause them. The method used in this study is the prioritization of medical and non-medical problems with the Delbecq method and the search for factors causing problems and their support through questionnaires and nutritional status checks on 177 respondents. The results are clear: diarrhea is the most prevalent medical problem in the Senteluk area, with 40% of respondents reporting it as a significant issue. This is followed by dengue hemorrhagic fever (33.33%), ARI/pneumonia (13.33%), dyspepsia (6.67%), and malaria (6.67%). The results were clear on non-medical issues as well. A whopping 79 people (44.63%) lack access to clean water, 87 (49.15%) have inadequate waste management, 98 (55.37%) lack proper liquid waste management (drainage), and 117 (66.1%) lack effective diarrhea prevention programs. Furthermore, the source of nutrition for residents is also not good resulting in Abnormal nutritional status 111 (62.71%). This is a significant factor influencing the incidence of diarrhea in Senteluk tourist village